Developing community-based health education strategies with family history: Assessing the association between community resident family history and interest in health education. (February 2021) - Prom-Wormley, Elizabeth C.; Clifford, James S.; Bourdon, Jessica L.; Barr, Peter; Blondino, Courtney; Ball, Kevin M.; Montgomery, Joshua; Davis, Jonathan K.; Real, Joseph E.; Edwards, Alexis C.; Thiselton, Dawn L.; Creighton, Gwen Corley; et al.
Abstract: Background: Family history (FH) is an underutilized genetically informative tool that can influence disease prevention and treatment. It is unclear how FH fits into the development of community-based health education. This study examines the role that FH plays in perceived threat and health education related to mental and chronic physical conditions in the context of the health belief model. Methods: Data were collected from 1, 048 adult participants aged 18–90 years. Approximately 76% of participants indicated African-American race/ethnicity and 35% had less than high school level education. Self-report data were collected on FH of four disorders: anxiety, depression, diabetes, and high blood pressure. Interest in receiving information regarding prevention as well as future testing efforts was assessed broadly. A series of logistic regressions examined the association between FH for each of the disorders and interest in receiving information on (1) prevention of diseases in general and (2) testing for diseases in general. These associations were also analyzed after accounting for the influence of perceived threat of conditions. Results: Interest in receiving general health education was significantly associated with FH of depression (OR = 2.72, 95% CI = 1.74–4.25), anxiety (OR = 2.26, 95% CI = 1.45–3.22), and high blood pressure (OR = 2.54, 95% CI = 1.05–6.12). After adjustment for perceived threat, the magnitude of these associations was reduced substantially. The associations between perceived threat and either interest in receiving information on disease testing or receiving general health education were strong and significant across all conditions (OR = 2.11–3.74). Discussion: These results provide evidence that perceived threat mediates the association between FH and engagement with health education. Currently available health education programs may benefit from considering the role of FH in an individual's motivation for participation in health education activities alongside other factors. Highlights: FH for depression, anxiety, and high blood pressure was associated with interest in receiving health education. Perceived threat mediated the relationship between FH and interest in receiving health education. Incorporating FH into community-based health education may develop awareness of several health conditions.